2013
DOI: 10.1097/jpn.0b013e3182a3cd42
|View full text |Cite
|
Sign up to set email alerts
|

A Midwifery-Led In-Hospital Birth Center Within an Academic Medical Center

Abstract: The University of California San Diego Community Women's Health Program (CWHP) has emerged as a successful and sustainable coexistence model of women's healthcare. The cornerstone of this midwifery practice is California's only in-hospital birth center. Located within the medical center, this unique and physically separate birth center has been the site for more than 4000 births. With 10% cesarean delivery and 98% breast-feeding rates, it is an exceptional example of low-intervention care. Integrating this pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Five included breastfeeding data from birth centers for analysis stratified breastfeeding data by specific birth setting. Two reported breastfeeding data from participants who birthed in birth center, home, and hospital settings (MacDorman & Declercq, 2016, 2019), two reported data from birth center and hospital settings (O'Hara et al, 2013; Thornton et al, 2017), and one study reported data from a birth center only (Perdion et al, 2013). Breastfeeding data from four of the AABC Perinatal Data Registry studies were not stratified by birth setting, but instead described cumulatively people who received care at AABC sites and birthed in birth center, hospital, or home settings (Alliman et al, 2019; Jolles et al, 2017, 2020; Stapleton et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five included breastfeeding data from birth centers for analysis stratified breastfeeding data by specific birth setting. Two reported breastfeeding data from participants who birthed in birth center, home, and hospital settings (MacDorman & Declercq, 2016, 2019), two reported data from birth center and hospital settings (O'Hara et al, 2013; Thornton et al, 2017), and one study reported data from a birth center only (Perdion et al, 2013). Breastfeeding data from four of the AABC Perinatal Data Registry studies were not stratified by birth setting, but instead described cumulatively people who received care at AABC sites and birthed in birth center, hospital, or home settings (Alliman et al, 2019; Jolles et al, 2017, 2020; Stapleton et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…MacDorman and Declercq (2019) reported breastfeeding initiation rates of 98.1% among birth center births and 82.0% among hospital births in 2016. Six studies reported about breastfeeding rates on postpartum discharge from a birthing facility, although none defined how many days after birth discharge occurred or how they defined any versus exclusive breastfeeding (Alliman et al, 2019; Jolles et al, 2017, 2020; Perdion et al, 2013; Stapleton et al, 2020; Thornton et al, 2017). Three studies described data about breastfeeding rates 4 to 6 weeks postpartum (Alliman et al, 2019; Nethery et al, 2021; Stapleton et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst the literature were descriptions of successful collaboration between midwives and obstetricians, both in Aotearoa NZ (Skinner, 2011;Skinner & Foureur, 2010) and overseas (Beasley et al, 2012;Chang Pecci et al, 2012;Ogburn et al, 2012;Perdion et al, 2013;Romijn et al, 2018;Stevens et al, 2012). Factors promoting effective communication included flat hierarchies and greater midwifery autonomy (Barker et al, 2019;Beasley et al, 2012;Downe et al, 2010;Skinner & Foureur, 2010), clear role definitions and boundaries (Munro et al, 2013;Norris, 2017), trust and respect (Chang Pecci et al, 2012;Downe et al, 2010;Lane, 2012), regular interprofessional interaction and use of structured communication tools (Marshall et al, 2009;Norris, 2017;Romijn et al, 2018), robust conflict resolution processes (Chang Pecci et al, 2012), shared education, (Meffe et al, 2012;Murray-Davis et al, 2014) and effective communication systems (Psaila et al, 2015;Schmied et al, 2015;Shaw et al, 2013).…”
Section: Previous Research On Professional Communication Between Primary Care Midwives and Obstetriciansmentioning
confidence: 99%